2020
DOI: 10.1183/23120541.00554-2020
|View full text |Cite
|
Sign up to set email alerts
|

Direct oral anticoagulant therapy in patients with morbid obesity after intermediate- or high-risk pulmonary emboli

Abstract: BackgroundThere is little reported on the efficacy and safety of direct oral anticoagulants (DOAC) in morbid obesity after venous thromboembolism (VTE).MethodsThis was an observational study of patients after intermediate- or high- risk pulmonary embolus (PE) who followed up in the University of Rochester Pulmonary Hypertension Clinic 2–4 months after the initial event with echocardiogram and V/Q imaging regardless of symptoms. Rates of recurrent VTE, thrombus resolution, and development of chronic thromboembo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In 2016, the International Society of Hemostasis and Thrombosis recommended against the use of direct oral anticoagulants in patients with BMI >40 or a weight >120 kg due to the lack of solid supportive clinical data [ 13 ]. Since then, a few studies have shown apixaban to be safe in patients with such extremes of weight without any dose adjustments [ 14 , 15 ], while others advocated for the use of drug-specific peak and trough levels [ 16 ]. However, there has not been any revision of the guidelines as of yet.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, the International Society of Hemostasis and Thrombosis recommended against the use of direct oral anticoagulants in patients with BMI >40 or a weight >120 kg due to the lack of solid supportive clinical data [ 13 ]. Since then, a few studies have shown apixaban to be safe in patients with such extremes of weight without any dose adjustments [ 14 , 15 ], while others advocated for the use of drug-specific peak and trough levels [ 16 ]. However, there has not been any revision of the guidelines as of yet.…”
Section: Discussionmentioning
confidence: 99%
“…In obese patients with acute VTE, there was no differences VTE recurrence (6.5 vs. 6.4%, p = 0.63), recurrence of PE (3.7 vs. 3.8%, p = 0.94), or DVT (3 vs. 3.5%, p = 0.56) between treatment with NOACs and warfarin. Bleeding was similar for both, NOAC and warfarin groups (1.7 vs. 1.2%, p = 0.31) [65]. Another observational study demonstrated NOAC to be effective and safe in morbid obese patients even after intermediate-or high-risk PE [65].…”
Section: Obesity and Vtementioning
confidence: 92%
“…Bleeding was similar for both, NOAC and warfarin groups (1.7 vs. 1.2%, p = 0.31) [65]. Another observational study demonstrated NOAC to be effective and safe in morbid obese patients even after intermediate-or high-risk PE [65].…”
Section: Obesity and Vtementioning
confidence: 92%
“…[12] Recent evidence also suggests that's DOACs may have similar risks of long-term complications including chronic thromboembolic pulmonary hypertension compared to warfarin in morbidly obese patients with intermediate or high-risk PE. [14] This study has several limitations. INR monitoring and warfarin dose adjustments were carried out in the community in line with routine clinical practice, and we were therefore unable to account for the effect of sub-or supratherapeutic INR on outcome measures.…”
mentioning
confidence: 92%
“…In a large registry based retrospective study of obese patients with all forms of VTE, S pyropoulos et al [ 12 ] also showed similar efficacy between rivaroxaban and warfarin with recurrent VTE rates of 16.8% and 15.9% at 12 months retrospectively. Recent evidence also suggests that's DOACs may have similar risks of long-term complications including chronic thromboembolic pulmonary hypertension compared to warfarin in morbidly obese patients with intermediate or high-risk PE [ 14 ].…”
mentioning
confidence: 99%